A supplier development adoption framework using expectancy theory. Issue 5 (3rd May 2016) - Chen, Liang; Ellis, Scott C.; Suresh, Nallan
Abstract : Purpose: – The purpose of this paper is to apply expectancy theory to advance a conceptual framework which identifies factors that motivate and affect the adoption of supplier development (SD) activities. Design/methodology/approach: – The authors conduct a comprehensive literature review to identify salient contributions and conceptual gaps within prior SD studies. These conceptual gaps motivate the use of expectancy theory and the broader management literature to develop a conceptual framework of SD adoption. Findings: – The study results in the development of a two-stage conceptual framework in which two behavioral constructs – SD expectancy and valence – play an important role in mediating the effects of activity-, firm-, interfirm-, and environment-level factors on the adoption of SD activities. Accordingly, the authors advance 11 testable propositions that underlie the logical development of the framework. Research limitations/implications: – The application of expectancy theory facilitates the integration of constructs culled from disparate theories into a cohesive conceptual framework. Highlighting the central role of motivational force, the conceptual development provides a behavioral explanation for the indirect effects of activity-, firm-, interfirm-, and environment-level factors on SD adoption. Practical implications: – The authors advance a set of factors associated with three successive stages of the SD planning process – partner selection, activity selection, and scope selection – that managers should consider when adopting a SD activity. Originality/value: – In contrast to prior research, which largely draws from economic or strategic theories, the authors employ a behavioral approach to advance a novel set of factors that influence SD adoption.